A giant tree in the rain forest - Morgan, Sally frey50 (Mankato, Minn. : Thameside Press, 2000)
Describes the variety of plant and animal life supported by the rain forest habitat, explaining how these habitats are threatened and how they can be preserved for the future.
Keywords: Rain forest ecology; Rain forests; Rain forest ecology; Rain forests; Ecology